Diabetes and COVID-19: Short- and Long-Term Consequences - Steenblock, Charlotte; Hassanein, Mohamed; Khan, Emran G.; Yaman, Mohamad; Kamel, Margrit; Barbir, Mahmoud; Lorke, Dietrich E.; Rock, John A.; Everett, Dean; Bejtullah, Saqipi; Heimerer, Adrian; Tahirukaj, Ermal; Beqiri, Petrit; Bornstein, Stefan R. (Hormone and Metabolic Research, 2022)
When the corona pandemic commenced more than two years ago, it was quickly recognized that people with metabolic diseases show an augmented risk of severe COVID-19 and an increased mortality compared to people without these comorbidities. Furthermore, an infection with SARS-CoV-2 has been shown to lead to an aggravation of metabolic diseases and in single cases to new-onset metabolic disorders. In addition to the increased risk for people with diabetes in the acute phase of COVID-19, this patient group also seems to be more often affected by long-COVID and to experience more long-term consequences than people without diabetes. The mechanisms behind these discrepancies between people with and without diabetes in relation to COVID-19 are not completely understood yet and will require further research and follow-up studies during the following years. In the current review, we discuss why patients with diabetes have this higher risk of developing severe COVID-19 symptoms not only in the acute phase of the disease but also in relation to long-COVID, vaccine breakthrough infections and re-infections. Furthermore, we discuss the effects of lockdown on glycemic control.
Keywords: diabetes mellitus type 1; diabetes mellitus type 2; COVID-19; metabolic syndrome; long-COVID